2019
DOI: 10.3847/1538-4365/aaef8e
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Ionized Gas of the Galaxy, Made with the Arecibo Telescope (SIGGMA): Inner Galaxy Data Release

Abstract: The Survey of Ionized Gas of the Galaxy, Made with the Arecibo telescope (SIGGMA) provides a fully-sampled view of the radio recombination line (RRL) emission from the portion of the Galactic plane visible by Arecibo. Observations use the Arecibo L-band Feed Array (ALFA), which has a FWHM beam size of 3 ′ .4. Twelve hydrogen RRLs from H163α to H174α are located within the instantaneous bandpass from 1225 MHz to 1525 MHz. We provide here cubes of average ("stacked") RRL emission for the inner Galaxy region 32 •… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…• 5, b = −0. • 6 may be affected by W51 (compare Figure 4 with the radio recombination line map of W51 presented by Liu et al 2019). The case L = 100 pc then implies a mean n e B ≈ 10 µG cm −3 .…”
Section: Discussionmentioning
confidence: 89%
“…• 5, b = −0. • 6 may be affected by W51 (compare Figure 4 with the radio recombination line map of W51 presented by Liu et al 2019). The case L = 100 pc then implies a mean n e B ≈ 10 µG cm −3 .…”
Section: Discussionmentioning
confidence: 89%
“…Wenger et al (2013 also studied the properties of helium and carbon RRL emission from the HRDS nebulae (including the H ii region G018.937−0.434a). Concerning the source G018.937−0.434a, line widths of hydrogen and helium lines were reported to be 23.83±0.05 and 16.31±0.85 km s −1 , respectively (Wenger et al 2013), which are smaller than the ones observed in supernova remnants (SNRs; i.e., > 50 km s −1 ; Liu et al 2019). Based on the properties of RRL emission (i.e., the 4 He + /H + ionic abundance ratio and line widths), the G18.937−0.434 (or G018.937−0.434a) was classified as a Galactic H ii region.…”
Section: Overview Of G1888−049mentioning
confidence: 95%
“…as G051.010+00.060 (Anderson et al 2014;Liu et al 2019), which is a source of thermal radio continuum emission.…”
Section: Arayamentioning
confidence: 99%